Optimization of high intensity ultrasound treatment of proso millet bran to improve physical and nutritional quality - Čukelj, Nikolina (Array, 2019)
Millet is an unexploited cereal with potential in the food industry due to its nutritional value and resistance to harsh climate conditions. Nutritious millet byproducts have a potential application in the development of functional cereal products, but require processing in order to improve their physical and nutritional quality. Therefore, we investigated high intensity ultrasound as a pretreatment to increase the amount of freely available bioactives from proso millet bran. We also analysed the effect of high intensity ultrasound on enzymatic browning, water retention and protein digestibility, which are crucial for the utilization in the bakery and pasta industry. A 15 % millet bran suspension in water was treated with 400-W ultrasound probe for 5, 12.5 or 20 min, with the 60, 80 or 100 % amplitude. High intensity ultrasound treatment with 80 % amplitude for 12.5 min improved most significantly the nutritive value.